Perioperative management of massive pulmonary hemorrhage after pulmonary endarterectomy - YILDIZELİ, BEDRETTİN; OLGUN YILDIZELİ, ŞEHNAZ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2018)
Background: This study aims to evaluate our approaches and outcomes in patients who developed hemoptysis following pulmonary endarterectomy. Methods: Pulmonary endarterectomy was performed in 460 patients at Kartal Kosuyolu Training and Research Hospital between March 2011 and September 2017. Clinical characteristics, perioperative management and postoperative outcomes of 10 patients (2.1%) (4 males, 6 females; mean age 48.3 +/- 16.5 years; range 21 to 76 years) with massive pulmonary hemorrhage following pulmonary endarterectomy were evaluated. Results: Mean period of diagnosis for chronic thromboembolic pulmonary hypertension was 17 +/- 13.6 months. All patients were New York Heart Association functional class II (n=2), III (n=5) or IV (n=3). For the treatment of massive pulmonary hemorrhage, intraoperative extracorporeal membrane oxygenation was used in six patients (60%), while conservative treatments were used in four patients (40%). In-hospital mortality rate was 50% (n=5); the causes for mortality were septic shock in two patients, multiple organ failure in two patients and intracranial hemorrhage in one patient. Survival was achieved in two patients on extracorporeal membrane oxygenation and three patients receiving conservative treatment. Functional and hemodynamic improvement was observed in all surviving patients. Conclusion: Despite the relatively low incidence of massive pulmonary hemorrhage after pulmonary endarterectomy, it is a potentially fatal complication. Our approach focuses on early diagnosis with a multidisciplinary team and management with bronchoscopy, bronchial blockers and use of extracorporeal membrane oxygenation. The choice of treatment depends on the site and origin of the hemorrhage, the availability of equipment and expertise, and the potential short- and long-term advantages and disadvantages.
Keywords: Chronic thromboembolic pulmonary hypertension; extracorporeal membrane oxygenation; massive pulmonary hemorrhage; pulmonary endarterectomy; INTERNATIONAL PROSPECTIVE REGISTRY; EXTRACORPOREAL LIFE-SUPPORT; THROMBOENDARTERECTOMY; HYPERTENSION; EXPERIENCE; OUTCOMES; ARTERY